Pengaruh Terapi Pijat Bayi Terhadap Kualitas Tidur Bayi Usia 1-12 Bulan di Puskesmas: PENGARUH TERAPI PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 1-12 BULAN DI PUSKESMAS - Somantri, Budi (Universitas 'Aisyiyah Bandung, 2018)
Absract Infant mortality in Indonesia is usually caused due to a number of factors the basic needs of a infant that was not met well. One of the basic needs to sleep. Sleep will stimulate development of brain and body. A worse of quality sleep will impact to the growth of infant. One of the implementation that can improve quality of sleep thorough infantâ€™s massage therapy. The purpose of this study was to effect of infantâ€™s massage therapy to the quality of sleep at ages 1-12 months. The sampling technique used purposive. Total samples consisted of 30 subjects who were divided into 15 respondents as a treatment group, and 15 respondents as a control group. Each experiment group was given a massage program for 6 times in a week Inclusion criteria that mother of respondents could communicate well, cooperative, and infants who become the respondents were healthy without congenital disease or physical defect, and the ages around 1-12 months. Research method used quasi experiment and design used posttest only control group on experiment group and control group. Results of statistical tests in this study showed the significant influences and there was average quality of sleep on the experiment and the control group after infants were getting massage with p value ( Ï = 0.002) < 0.05. Based on the results of this research, it was suggested to perform the measurement of infant quality of sleep by using pre test, using more accurate parameters, and increase the number of research samples. Keywords: infant massage therapy, quality of sleep